A facile and combined methodology to fabricate sputtered thin film micro-patterns for heater/sensor applications utilizing CO2 laser-cut masks. (2nd September 2021) - Hasan, Mohammed Adnan; Prajwal, K.; Sahu, Dwarika Nath; Prasad, Arpana; Dey, Arjun; Rajendra, A.
ABSTRACT: We propose a facile and combined methodology to develop magnetron sputtered various metals and alloy (e.g. tungsten, tin and nichrome), and metal oxide (indium tin oxide) thin film-based micro-patterns deposited on flexible and rigid substrates utilizing reusable patterned mask. CO2 laser-cut glass-based mask is fabricated and assembled with the substrates for pattern printing by sputtered thin film deposition technique. Fabrication of mask is adopted with the rapid CO2 laser-cut process aided with computer-aided design software. The laser-cut glass-based mask can easily fix on any type of substrates and any resistive materials deposition can be carried out. Currently, the developed thin film micro-patterns show good uniformity, dense morphology and without sign of any discontinuity. Finally, a successful functional characterization of a typical nichrome line-heater also confirms the feasibility and proof of concept of the present proposed approach that is much facile, less time-consuming and economical.